Oriented Incidence Colourings of Digraphs - Duffy Christopher; MacGillivray Gary; Ochem Pascal; Raspaud André (Discussiones Mathematicae Graph Theory, 2019)
Brualdi and Quinn Massey [6] defined incidence colouring while study- ing the strong edge chromatic index of bipartite graphs. Here we introduce a similar concept for digraphs and define the oriented incidence chromatic number. Using digraph homomorphisms, we show that the oriented inci- dence chromatic number of a digraph is closely related to the chromatic number of the underlying simple graph. This motivates our study of the oriented incidence chromatic number of symmetric complete digraphs. We give upper and lower bounds for the oriented incidence chromatic number of these graphs, as well as digraphs arising from common graph constructions and decompositions. Additionally we construct, for all k > 2, a target digraph Hkfor which oriented incidence k colouring is equivalent to homomorphism to Hk.